Antifungal Combination of Ethyl Acetate Extract of Poincianella pluviosa (DC.) L. P. Queiros Stem Bark With Amphotericin B in Cryptococcus neoformans - Andriani, Gabriella Maria; Morguette, Ana Elisa Belotto; Spoladori, Laís Fernanda Almeida; Pereira, Patrícia Morais Lopes; Cabral, Weslei Roberto Correia; Fernandes, Bruna Terci; Tavares, Eliandro Reis; Almeida, Ricardo Sérgio; Lancheros, Cesar Armando Contreras; Nakamura, Celso Vataru; Mello, João Carlos Palazzo; Yamauchi, Lucy Megumi; et al. (Frontiers in Microbiology, 2021)
Cryptococcus neoformans is the leading cause of cryptococcosis, an invasive and potentially fatal infectious disease. Therapeutic failures are due to the increase in antifungal resistance, the adverse effects of drugs and the unavailability of therapeutic regimens in low-income countries, which limits the treatment of cryptococcosis, increasing the morbidity and mortality associated with these infections. Thus, new antifungal drugs and innovative strategies for the cryptococcosis treatment are urgently needed. The aim of the present study was to evaluate the effect of ethyl acetate fraction (EAF) of Poincianella pluviosa stem bark on planktonic and biofilm mode of growth of C. neoformans. In addition, the interaction between the EAF and amphotericin (AmB) was evaluated in vitro and in Galleria mellonella infection model. Minimum inhibitory concentrations (MIC) of ethyl EAF ranged from 1000.0 to >1000.0 μg/mL, and > 1000.0 µg/mL for planktonic and sessile cells, respectively. The combination between EAF and AmB exhibited a synergistic fungicidal activity towards C. neoformans, with fractional inhibitory concentration index (FICI) ranging from 0.03 to 0.05 and 0.07 to 0.28 for planktonic and sessile cells, respectively. Moreover, EAF alone or combined with AmB prolonged the survival rate of C. neoformans-infected G. mellonella larvae. These findings indicate that P. pluviosa may be an important source of new compounds which can be used as a fungal-specific adjuvant for the treatment of cryptococcosis.